Competitividad en micro y pequeñas empresas en el sector lácteo del Cantón Latacunga - Heredia Cuzco, Evelyn Silvana (2019)
Nowadays, companies depend on internal and external factors that allow them to develop and stay in the market, for this reason, it is necessary to determine how hard they are before the competition. In this research the competitiveness index of the micro and small enterprises of the dairy sector at Latacunga Canton was estimated. When there are few studies in the sector, both the government and micro and small businesses ignore the factors that make them more or less competitive, thus it is necessary to consider external factors such as: economic; infrastructure; socio-demographic; institutional and environmental factors and internal factors as: strategic planning, production and operation, quality, marketing, human resources, finance, accounting and innovation. For this, the methodology of Territorial Competitiveness of Fonseca Hernández was adapted and the cantonal competitiveness index was estimated using secondary data, through the 5 aforementioned components. After that, the business competitiveness index was estimated by adapting the BID's Competitiveness Map, using primary data collected through a questionnaire in which 7 internal variables of the company were studied. Once the indices of cantonal competitiveness of 0.66 and business competitiveness of 0.49 were obtained; the competitiveness index of micro and small enterprises in the dairy industry at Latacunga Canton was constructed with a result of 0.57.